An inverse Q filtering method with adjustable amplitude compensation operator - Zhao, Yan (Journal of applied geophysics, 2023)
The generalized stable inverse Q filtering method can flexibly select the intensity and frequency bandwidth of amplitude compensation operator according to the signal-to-noise ratio (SNR) of seismic data. When processing noisy seismic data, the method can avoid enhancing some noise energy by adjusting parameters. However, this method still faces the problem of noise amplification when the SNR of seismic data is low. In order to solve this problem, this paper proposes an adjustable amplitude compensation operator, which can suppress part of the high frequency noise energy effectively without affecting the intensity of the amplitude compensation by introducing a dynamically adjustable amplitude compensation curve. Combining this operator with the generalized stable inverse Q filtering algorithm, an inverse Q filtering method with adjustable amplitude compensation operator is developed. Compared with the generalized stable inverse Q filtering method, this method has the ability of adjustable amplitude compensation and adjustable noise suppression. When inverse Q filtering is performed on the seismic records, the compensation strategy can be more flexible according to its quality and processing requirements. In addition, this method almost not introduce extra calculation cost, and has the characteristics of simplicity and high efficiency. Theoretical and practical seismic records show that the proposed method can further improve the SNR and resolution of seismic records after inverse Q filtering. •I propose a new adjustable amplitude compensation operator and develop an inverse Q filtering method with the new operator.•This inverse Q filtering method has the ability of adjustable amplitude compensation and adjustable noise suppression.•The method can provide flexible compensation strategy according to the quality and processing requirements of seismic data.